Reviews of recent publications (Studies in 20th & 21st Century Literature, 2011)
Paul Kong. The Raiders and Writers of Cervantes’ Archive: Borges, Puig, and García Márquez by José Fernando Olascoaga J. J. Long. W. G. Sebald: Image, Archive, Modernity by Helen Finch Andrew Baruch Wachtel. Plays of Expectations: Intertextual Relations in Russian Twentieth-Century Drama by Volha Isakava David Jenemann. Adorno in America by Ruth Starkman Philippe Lacoue-Labarthe. Heidegger and the Politics of Poetry by Derek Hillard Horacio Legras. Literature and Subjection: the Economy of Writing and Marginality in Latin America by Abraham Acosta Hélène Cixous. Love Itself in the Letterbox by Natalie Edwards Zulema Moret. Esas niñas cuando crecen, ¿Dónde van a parar? by Julia A. Kushigian Terry Eagleton. Trouble with Strangers: A Study of Ethics by Melanie Collado Dominic Moran. Pablo Neruda by Donald Shaw
Keywords: Borges; Puig; García Márquez; W. G. Sebald; modernity; Russian Twentieth-Century Drama; Heidegger; Pablo Neruda